Recent Bioinformatic Progress to Identify Epigenetic Changes Associated to Transposable Elements - Lerat, Emmanuelle (Frontiers in Genetics, 2022)
Transposable elements (TEs) are recognized for their great impact on the functioning and evolution of their host genomes. They are associated to various deleterious effects, which has led to the evolution of regulatory epigenetic mechanisms to control their activity. Despite these negative effects, TEs are also important actors in the evolution of genomes by promoting genetic diversity and new regulatory elements. Consequently, it is important to study the epigenetic modifications associated to TEs especially at a locus-specific level to determine their individual influence on gene functioning. To this aim,this short review presents the current bioinformatic tools to achieve this task.